Saudi labor market requirements between reality and the challenges of higher education to achieve Vision 2030: Japan's experience as a model - Alqarawi, Hayat (Journal of Economic, Administrative and Legal Sciences, 2022)
The current study aimed to identify the requirements of the Saudi labor market and the reality and challenges of Saudi higher education to achieve the Kingdom's 2030 vision. This research relied on the documentary analytical method, by analyzing the reality of higher education, development plans, the Kingdom's vision 2030 and the extent to which education outputs are compatible with the labor market. To achieve the study's goal, the Japanese experience was used.This study relied on the documentary analytical method, by analyzing the reality of Saudi higher education, development plans, and the Kingdom’s vision 2030. The study included a number of documents:- Development plans for the Kingdom of Saudi Arabia- The future plan for university education in the Kingdom of Saudi Arabia: Afaq project- The Kingdom's Vision 2030- A number of Saudi and Japanese researches and studiesA comparison was made between the experiences of Saudi Arabia and Japan to align the outputs of education with the labor market, recommendations were presented to match the outputs of higher education with the actual needs of the Saudi labor market.
Keywords: higher education; challenges; the Saudi labor market; adapting education to the labor market